I ndigenous peoples in the chilean constituent process: challenges of the process and main proposals - Figueroa Huencho, Verónica (Política. Revista de Ciencia Política, 2020)
Since the creation of nation-states, Indigenous Peoples have been forced to adopt ways of life alien to their cultures, being forced to join projects of society constriction that have not allowed their adequate participation and political representation. In this way, the discussion around the new Political Constitution in Chile finds Indigenous Peoples in a precarious system of rights recognition, which limits their possibilities of participating on equal terms with the rest of the citizenry, especially through the mechanism of reserved seats and the incorporation into the Constitution of its proposals for a plurinational State and autonomy. This article addresses these concepts, their scope and tensions, as well as their implications in the installation of an intercultural dialogue in the future Constitutional Convention.